Algunas consideraciones sobre una posible etiología de las malas prácticas y la corrupción en el ámbito de las administraciones públicas - Nevado-Batalla Moreno , Pedro T. (2019)
From a brief analysis of each day reality in Public Administration, we could identify proposals which promote the existence of bad practices or corruption cases. These proposals, which reject such kind of practices, they also, unconsciously or consciously, cause a break in the state of Law, facilitating and generating contradictions and legal perplexity. Maybe the answers to these bad practices or corruption cases, which are causing severe problems to the state of Law and to proper democracy, may be much nearer than ever. In this essay there are briefly treated some causes that we understand integrate the etiology of a severe problem, which seriously endangers administrative organizations